Costa Rica´s enhanced 2020 Nationally Determined Contribution (NDC) developed using CCAFS future scenario approach - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
During 2020, the MINAE used the CCAFS future scenarios methodology to enhance the country's NDC. UCI designed and facilitated an online participatory consultation in which more than 350 stakeholders participated to develop multiple sets of future scenarios based on contextual uncertainties that could positively or negatively influence Costa Rica´s ability to reach climate goals. These scenarios were used in all NDC sectors to critically discuss and robust the countries´ intended measures to reduce emissions and increase resilience to climate change.